MicroRNA profiles of MS gray matter lesions identify modulators of the synaptic protein synaptotagmin‐7 - Fritsche, Lena (Brain Pathol, 2019)
We established microRNA (miRNA) profiles in gray and white matter multiple sclerosis (MS) lesions and identified seven miRNAs which were significantly more upregulated in the gray matter lesions. Five of those seven miRNAs, miR‐330‐3p, miR‐4286, miR‐4488, let‐7e‐5p, miR‐432‐5p shared the common target synaptotagmin7 (Syt7). Immunohistochemistry and transcript analyses using nanostring technology revealed a maldistribution of Syt7, with Syt7 accumulation in neuronal soma and decreased expression in axonal structures. This maldistribution could be at least partially explained by an axonal Syt7 transport disturbance. Since Syt7 is a synapse‐associated molecule, this maldistribution could result in impairment of neuronal functions in MS patients. Thus, our results lead to the hypothesis that the overexpression of these five miRNAs in gray matter lesions is a cellular mechanism to reduce further endogenous neuronal Syt7 production. Therefore, miRNAs seem to play an important role as modulators of neuronal structures in MS.